Mathematical Computational Thinking : Systematic Literature Review - Chelsi Ariati; Aswin Aswin (EduMa: Mathematics education learning and teaching, 2023)
One of the key math learning goals that students at school must attain is mathematical computational thinking. This research attempts to review research on mathematical computation thinking done between 2018 and 2023. A systematic review of the literature (SLR) was conducted on all papers listed in Google Scholar, Semantic, and ERIC. The PRISMA protocol served as a guide for the research instrument while the search technique was modified to the selection criteria. The year of publication, education level, research class, demographics, journal indexer, and content studied are the variables in this study. The presentation of all data is quantitative descriptive. The findings of the SLR investigation indicate that in 2022 there will be a large publication of papers about students' mathematical computational thinking. The majority of these studies are conducted in grades VIII and IX in junior high schools. The study of numbers and algebraic concepts was very prevalent in Java and Bali. Future educators and researchers are advised to conduct additional research on computational thinking in mathematics starting at the elementary school level, outside of Java and Bali, on subjects other than algebra and numbers as well as research-related computational thinking indicators.